2016
DOI: 10.1074/jbc.m116.716902
|View full text |Cite
|
Sign up to set email alerts
|

CerS6 Is a Novel Transcriptional Target of p53 Protein Activated by Non-genotoxic Stress

Abstract: Our previous study suggested that ceramide synthase 6 (CerS6), an enzyme in sphingolipid biosynthesis, is regulated by p53: CerS6 was elevated in several cell lines in response to transient expression of p53 or in response to folate stress, which is known to activate p53. It was not clear, however, whether CerS6 gene is a direct transcriptional target of p53 or whether this was an indirect effect through additional regulatory factors. In the present study, we have shown that the CerS6 promoter is activated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Mechanistically, melanoma cells exhibited increased platelet secretory ASMase activity, which induced C16 ceramide formation and led to activation and clustering of α5β1 integrin on melanoma cells, thereby promoting cancer cell adhesion and metastasis 47 . These data suggest that although induction of ASMase in cancer cells results in apoptosis, systemic ASMase activation in platelets leads to increased melanoma metastasis, highlighting the importance of cell-type-specific expression of enzymes involved in ceramide signalling in inducing cell death versus increasing survival and/or migration, similar to CERS6–C16 ceramide signalling in lung cancer (apoptotic) 35 versus HNSCC (survival) 41 cells.…”
Section: Sphingolipid Metabolism and Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…Mechanistically, melanoma cells exhibited increased platelet secretory ASMase activity, which induced C16 ceramide formation and led to activation and clustering of α5β1 integrin on melanoma cells, thereby promoting cancer cell adhesion and metastasis 47 . These data suggest that although induction of ASMase in cancer cells results in apoptosis, systemic ASMase activation in platelets leads to increased melanoma metastasis, highlighting the importance of cell-type-specific expression of enzymes involved in ceramide signalling in inducing cell death versus increasing survival and/or migration, similar to CERS6–C16 ceramide signalling in lung cancer (apoptotic) 35 versus HNSCC (survival) 41 cells.…”
Section: Sphingolipid Metabolism and Cancermentioning
confidence: 88%
“…Approximately 50% of mice with germline loss of Cers2 , which is involved in reduction of long-chain (C22–24) ceramides, developed pheochromocytoma owing to possible defects in apoptosis 34 . Moreover, CERS6-generated C16 ceramide was identified as a transcriptional target of p53 that is activated by non-genotoxic folate stress to induce cell death in p53 wild-type human lung cancer cells 35 . CERS6-generated C16 ceramide was also shown to increase tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) sensitivity by inducing nuclear translocation of caspase 3 in colon cancer cells 36 .…”
Section: Sphingolipid Metabolism and Cancermentioning
confidence: 99%
“…EMSA provides a tool for investigation of protein and DNA interaction (Fekry et al., ; Wang et al., ). In most EMSA assays, nuclear extract was directly incubated with DNA probes that were designed and synthesized to cover putative TFBSs (Fekry et al., ; Wang et al., ). Transcription factor in the nuclear extract can bind to the DNA probe that contains the real targeted TFBS.…”
Section: Discussionmentioning
confidence: 99%
“…Another ceramide synthase, CerS6, was recently found to be directly transcriptionally activated by p53 via a noncanonical binding site, 11 nucleotides upstream of transcription start site (Fekry, Jeffries, et al, 2016). In contrast to the upregulation of ceramide synthases, SPHK1, a sphingolipid enzyme balancing the ceramide/S1P rheostat (Baran et al, 2007), was shown to be downregulated by p53 (Heffernan-Stroud et al, 2012; Taha et al, 2004).…”
Section: P53 and Ceramide Pathwaysmentioning
confidence: 99%